Cu atoms suppress misfit dislocations at the β″/Al interface in Al–Mg–Si alloys. (1st January 2016) - Saito, Takeshi; Ehlers, Flemming J.H.; Lefebvre, Williams; Hernandez-Maldonado, David; Bjørge, Ruben; Marioara, Calin D.; Andersen, Sigmund J.; Mørtsell, Eva A.; Holmestad, Randi
Graphical abstract: Abstract: The Cu interactions with the Al–Mg–Si alloy main hardening phase β″ are investigated in atomic scale, by using experimental and simulated high angle annular dark-field scanning transmission electron microscopy techniques and density functional theory calculations. Cu is located at or near the β″/Al interface, with the misfit dislocations normally observed for a precipitate of this size being absent. It is proposed that the small Cu volume is crucial to this mechanism. Present supercell based calculations cannot fully model these interactions.